Платонівська критика мистецтва в контексті становлення дискурсу репрезентацій - Головей, Вікторія (Видавництво Львівської політехніки, 2014)
На основі докладного аналізу платонівської теорії мистецтва описано генезис дискурсу образотворчої репрезентації в європейській філософсько-естетичній традиції. Обґрунтовується, що саме Платон започатковує есенціальний дискурс і в його координатах – сферу репрезентації, у якій будь-яка річ або явище трактується як адекватне або неадекватне зображення-представлення певної сутності. Досліджуються витоки проблематики “недовіри мистецтву”, “симулякрів і симуляції”, а також магістральних тенденцій в осмисленні репрезентативної сутності мистецтва, які визначатимуть суперечливе ставлення до художньої образотворчості від античних часів до сучасних. In this article the genesis of discourse of pictorial representation in the European philosophical and aesthetic traditions is investigated, on the basis of detailed analysis of Plato's art theory. It has been substantiated that Plato did established essential discourse and in its coordinates – the scope of representation in which any thing or phenomenon have been treated as adequate or inadequate pictorial representation of a certain essence. We investigate the origins ofsuch problems as “distrust of art”, “simulacra and simulation” and the main trends in comprehension of the representative nature of art that determines the contradictory attitude to artistic depiction from ancient times to nowadays. Іt is assumed that the theory of representation has been a mandatory component of any metaphysics. While philosophy starts searching for absolute principles and the methods relating immanence and transcendence, the ideal and the real, and trying to distinguish authentic and simulation, the concept of representation becomes a necessary condition of ontological distinction. Representation paves the way to ontology, because it does allows keeping the elusiveness of reality in continuous mode of selfrepresentation, the dialectic of the visible and invisible, presence and absence. Focusing on the contrast of the idea and its figurative embodiment, Plato establishes a kind of iconology based on the ontological distinction between prototype and the infinite gradations of its possible representations. In the measurement of the world of representations the problem of the validity of image is associated with the differentiation of the nature and visibility, the original and copies, the prototype and similarity. The difference is determined by the extent essential similarity to the original, or by the distinction between presentation and representation. Such approach is characterized by an ontological contradistinction between the prototype and its artistic and imaginative representations as substance and only visibility, also by recognition of ontological inferiority of images and denial of its opportunities for adequate representation of nature. Despite the apology of imitative arts was developed by Aristotle, Plotinus and later thinkers, the most serious attempts to further criticism of art in its relation to the truth were based on the logic of Plato's argument.
Plato's critique of the arts in the context of the formation of discourse of representation
Keywords: мистецтво; образ; симулякр; репрезентація; дискурс; art; image; simulacrum; representation; discourse